“Everywhere is Warmer than the house”: ‘Traumaculture’ in Laura Wade’s Colder Than Here - Gülter, Isıl Şahin (My University, 2021)
Contemporary British theatre is a crucial avenue for staging trauma as theatre\rprovides both the potential of emotional identification and critical perspective.\rBy making use of the unique possibilities of embodied performance, theatre\rallows for a safe space in which traumatic suffering can be reconfigured. Drawing\ron the notion of Roger Luckhurst’s ‘traumaculture,’ this paper interrogates the\rextent to which contemporary British playwright Laura Wade’s one-act play,\rColder Than Here (2005), situates current traumatic experiences within social\rand cultural contexts. This paper deals with terminal disease increases, familial\rdysfunction, and ecological degradation as traumatic experiences that permeate\rdaily existence. Therefore, by bringing into the spotlight the contemporary\rdefinition of trauma and traumaculture, this paper aims at exploring how\rColder Than Here reflects multifaceted engagements with traumatic cultural\rexperiences onstage with a focus on a middle-class English family.
Keywords: Film; Radyo; Televizyon; Beşeri Bilimler; Edebiyat; Psikoloji; Tiyatro; Edebi Teori ve Eleştiri